Impure Subjects within Power Structures: Female Subjectivity in Anuradha Roy’s All the Lives We Never Lived - Yan, Ziwei; Yin, Jing (Journal of Literary Studies, 2025)
Anuradha Roy’s novel All the Lives We Never Lived explores female subjectivity during the Indian independence movement. This article applies Irene Gedalof’s feminist theoretical framework, particularly her critique of purity and her emphasis on the mobility and positionality of subjectivity, to examine two female characters from different backgrounds in the novel: the traditional widow, Lipi, and the Westernised nomadic figure, Gayatri. The analysis demonstrates that female agency is not merely defined by acts of resistance, but is produced through complex processes of power, discipline, and negotiation. These processes are often marked by contradictions, sacrifices, and even physical disappearance.